Penentuan Ekstrakurikuler Siswa Sesuai Minat Bakat dengan Case-Based Reasoning dan Certainty Factor - Arjun Sirojul Anam; Faris Muslihul Amin; Mujib Ridwan (Maranatha University Press, 2021)
Extracurricular activities at MAN 1 Lamongan are still determined without any support from the system. Students are only given extracurricular information and can register according to the conditions if interested. This makes the extracurricular that students have chosen does not fully match their abilities. The result is a decrease in the number of members who are active in extracurricular activities due to loss of interest. A web-based system was developed to assist MAN 1 Lamongan in determining extracurricular according to interests and talents. Case-Based Reasoning (CBR) is the system framework and Certainty Factor (CF) is the algorithm for determining the certainty value. The result is that with test data of 68 students, the system recommends extracurricular well. Testing with Confusion Matrix obtained precision level of 96.03% (high), recall of 99.4% (high), accuracy of 95.76% (high)